Professionalism in the teaching of the elderly health care during nursing graduation - João Paulo Xavier Silva; Nayara Santana Brito; Thiáskara Ramile Caldas Leite; Evanira Rodrigues Maia; Maria de Fátima Antero Sousa Machado; Maria do Socorro Vieira Lopes (Rev Rene)
Objective: to understand the attributes formulation for the professionalism education in the teaching of the elderly health care during the nursing graduation. Methods: this is a qualitative study carried out in four educational institutions to evaluate educational planning documents of the elderly health subject. The lexical type content analysis was used through the Lexical Contextual Analysis software of a Set of Text Segments. Results: two discursive classes emerged: Perspective for theoretical-practical learning and Content-based teaching. The categories show an educational model anchored in the transmission of content with little emphasis on teaching by competence and training of skills essential for the development of the nurse professional identity in the elderly´s health. Conclusion: in the educational planning documents, it is not possible to observe the attributes for the professionalism education in the formation of an identity profile in a clear and structured way focused on the elderly´s health.